Studies on protective mechanisms of four components of green tea polyphenols against lipid peroxidation in synaptosomes - Guo, Qiong; Zhao, Baolu; Li, Meifen; Shen, Shengrong; Xin, Wenjuan (Biochimica et biophysica acta, 1996)
The comparison of the protective effects of four components of ‘green tea polyphenols’ (GTP) — (−)-epigallocatechin gallate, EGCG; (−)-epicatechin gallate, ECG; (−)epigallocatechin, EGC; and (−)epicatechin, EC — against iron-induced lipid peroxidation in synaptosomes showed that: (1) the inhibitory effects of those compounds on TBA reactive materials from lipid peroxidation decreased in the order of EGCG > ECG > EGC > EC; (2) the scavenging effects of those compounds on lipid free radicals produced by lipid peroxidation could be classified as follows: ECG > EGCG > EC > EGC. Furthermore, we investigated the iron-chelating activity and the free radical scavenging activity of those compounds as their protective mechanisms against lipid peroxidation in synaptosomes. As for the iron-chelating activity, the ratio of EGC, EGCG, ECG or EC to iron(III) was 3:2, 2:1, 2:1 and 3:1, respectively. The hydroxyl radical (HO) scavenging activity of those compounds was investigated in a photolysis of the H202 system. It was found that their ability to scavenge hydroxyl radicals decreased in the order of ECG > EC > EGCG ≫ EGC. It was also found that they could scavenge lipid free radicals in the lecithin/lipoxidase system and their scavenging activity was classified as follows: ECG > EGCG ≫ EGC > EC. Moreover, we found that their antioxidant active positions were different from each other and the stability of the semiquinone free radicals produced by those compounds in NaOH solution decreased in the order of EGCG > ECG ≫ EC. The results indicated that the ability of those compounds to protect synaptosomes from the damage of lipid peroxidation initiated by Fe2+/Fe3+ was dependent not only on their iron-chelating activity and free-radical scavenging activity, but also on the stability of their semiquinone free radicals.